2021
DOI: 10.30802/aalas-jaalas-20-000082
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Buprenorphine and Sustained-release Buprenorphine in Common Marmosets (Callithrix jacchus)

Abstract: Buprenorphine is an essential component of analgesic protocols in common marmosets (Callithrix jacchus). The use of buprenorphine HCl (BUP) and sustained-release buprenorphine (BSR) formulations has become commonplace in this species, but the pharmacokinetics have not been evaluated. Healthy adult (age, 2.4 to 6.8 y; 6 female and 6 male) common marmosets were enrolled in this study to determine the pharmacokinetic parameters, plasma concentration–time curves, and any apparent adverse effects of these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Compared to the common marmoset, the plasma half-life in cynomolgus monkeys of 42.6 h is longer than that of the common marmoset with either BUP-SR or BUP-XR. 10,12 In the study by Nunamaker, it was reported that there was no statistical difference in the observed half-life for either rhesus or cynomolgus monkeys. 14 This may hold a particular advantage as data from the present study in male cynomolgus monkeys suggests that it may be safe to extrapolate dose regimens for this formulation of XR BUP to rhesus monkeys.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared to the common marmoset, the plasma half-life in cynomolgus monkeys of 42.6 h is longer than that of the common marmoset with either BUP-SR or BUP-XR. 10,12 In the study by Nunamaker, it was reported that there was no statistical difference in the observed half-life for either rhesus or cynomolgus monkeys. 14 This may hold a particular advantage as data from the present study in male cynomolgus monkeys suggests that it may be safe to extrapolate dose regimens for this formulation of XR BUP to rhesus monkeys.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, no abnormal behaviors or clinical signs, or injection site reactions were observed. By comparison, PK studies in the common marmoset 10,11 using a polymer‐based compounded long‐acting SR‐BUP demonstrated mild localized erythema and swelling of tissues around the injection site, which was reversible over time. This was not observed with Ethiqa XR in marmosets 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,51,52 Although dose-dependent respiratory depression and sedation are possible, many studies have established buprenorphine to be safe and effective in common laboratory animal species including mice, rats, and non-human primates. 1,4,12,14,16,27,33,38 Despite the plethora of information regarding buprenorphine use in rodents, there is little information on adequate buprenorphine use in swine. The reported dose for buprenorphine HCl in swine is wide and ranges from 0.01-0.1 mg/kg with a dosing frequency of twice or three times daily.…”
Section: Introductionmentioning
confidence: 99%
“…10,51,52 Although dose-dependent respiratory depression and sedation are possible, many studies have established buprenorphine to be safe and effective in common laboratory animal species including mice, rats, and non-human primates. 1,4,12,14,16,27,33,38…”
Section: Introductionmentioning
confidence: 99%